"I Have to Listen to This Old Body": Femininity and the Aging Body. (13th October 2017) - Rutagumirwa, Sylivia Karen; Bailey, Ajay
Abstract: Background and Objectives: This study explores how older women with low socioeconomic status living in rural Tanzania give meaning to their (aging) body in relation to the ideals of femininity. Research Design and Methods: Ten qualitative in-depth interviews and 10 focus group discussions ( N = 60) were conducted among women aged 60 and older. Results: The findings reveal that older women perceive their aging body as "a burden." This characterization of the body is linked to the inability of the aging body to live up to the women's gendered lives. The conflict between their physical limitations and the desire to perform gendered tasks (internalized feminine habitus) affect the women's process of self-identification. This led to emotional distress and subsequently threatened their survival and well-being. Discussion and Implications: The results suggest that older women need to be supported through interventions that are tailored to their cultural and socioeconomic context.